Estimation of leaf loss rate in pest damaged larch forests using Sentinel-2 satellite data - Ariunaa, Mungunkhuyag; Dashzeveg, Ganbat; Jun, Huangxiao; Yunhai, Bao; Dorjsuren, Altantuya; Rentsenduger, Boldbaatar (Mongolian Journal of Geography and Geoecology, 2022)
In recent years, the research on remote sensing monitoring of forest damage has made great progress. The monitoring of forest pest severity using remote sensing methods that are sensitive to the spatiotemporal variations of canopy degradation and leaf lost rate. In this study, two typical conifer pests as Erannis Jacobsoni Djak.(EJD) and Pendrolimus Sibiricus Tschtv.(PST) are selected for forest area of Binder and Baruunburen in Mongolia. based on the star ground combination model, the spectral reflectance are simulated from Sentinel-2A image, and the spectral index (SI) and spectral derivative feature (SDF) are calculated, the sensitive spectral features of SI and SDF are extracted by combining threshold method and SPA algorithm, and then establish the discrimination model of different pest types based on random forest(RF). At the same time, the monitoring models of pest indicators were constructed, and the severity of pests were identified by FCM fuzzy clustering. The accuracy of RF model based on Sentinel-2A remote sensing simulation data is significantly improved. The spectral index and derivative spectral features of Sentinel-2A remote sensing simulation data have significant sensitivity to the two pest indicators. Using the spectral features of remote sensing simulation data, the indicators of conifer pest can be identified by RF and PLSR algorithm. In the identification of conifer pests based on the non-simulated Sentinel-2A remote sensing data, the estimation accuracy of the two pests' leaf loss rate is the highest. Сентинел-2 хиймэл дагуулын мэдээ ашиглан хортонд нэрвэгдсэн шинэсэн ойн шилмүүсний алдагдлыг тооцох ХУРААНГУЙ Ойд учирсан хохирол, хор хөнөөлийг зайнаас тандах аргаар судлах судалгаа сүүлийн жилүүдэд ихээхэн ахиц дэвшил гаргаж байна. Зайнаас тандан судлах аргуудыг ашиглан ойн хортон шавжийн ноцтой байдлын хянах, шилмүүсний алдагдлыг тооцох судалгааг Хэнтий аймгийн Биндэр, Сэлэнгэ аймгийн Баруунбүрэн сумын Якобсоны төөлүүр эрвээхэй болон Сибирийн хүр эрвээхэйн хөнөөлд өртсөн шилмүүсэн ойд хийсэн. Хиймэл дагуулын мэдээ болон газар дээрх спектрийн ойлтын үр дүнг хослуулсан загварт үндэслэн Sentinel-2A зургаас спектрийн индекс (SI) болон спектрийн дериватив шинж чанарыг (SDF) тооцоолж, SI болон SDF-ийн спектрийн онцлог шинж чанарыг хослуулан гаргаж авсан. Дараа нь SPA алгоритм болон санамсаргүй ойн (RF) загварчлал дээр үндэслэн өөр төрлийн хортон шавжийг ялгах загварыг бий болгосон. Үүний зэрэгцээ хортон шавжийн үзүүлэлтүүдийн хяналтын загваруудыг гаргаж, хортон шавжийн шилмүүсэнд учруулсан хөнөөлийн байдлыг FCM тодорхой бус кластерчлалаар тодорхойлсон. Үр дүнгээс харахад Sentinel-2A хиймэл дагуулын мэдээний симуляцийн өгөгдөлд суурилсан RF загварын нарийвчлал мэдэгдэхүйц сайжирсан. Зайнаас тандан судлах аргаар симуляци хийсэн өгөгдлийн спектрийн шинж чанарыг ашиглан шилмүүст ойн хортон шавжийн үзүүлэлтүүдийг RF болон PLSR алгоритмаар тодорхойлох боломжтой. Sentinel-2A хиймэл дагуулын загварчлаагүй мэдээлэлд үндэслэн шилмүүст модны хортон шавжийг тодорхойлоход хоёр хортон шавжийн навчны алдагдлын тооцооны нарийвчлал хамгийн өндөр байна. Түлхүүр үг: Сентинел-2 хиймэл дагуул, Зайнаас тандан судлал, Мониторинг, Ялгах загвар, Шилмүүсний алдагдал, Якобсоны төөлүүр эрвээхэй, Сибирийн хүр эрвээхэй